Skilled Labour Migration and Firm Performance: Evidence from English Hospitals and Brexit - Kai Fischer (Center for Economic Studies and ifo Institute (CESifo), 2023)
How do skilled migrant workers affect firms' performance and output? I estimate the causal effect of EU nurse withdrawal after the Brexit referendum on the performance of English hospitals. Exploiting variation in the reliance on EU workers across hospital providers in pre-referendum years, I find that providers with a mean share of EU nurses before the referendum persistently face 2% more hospital-related deaths after the referendum. This translates to 5,900 additional hospital-related deaths p.a. in England. Unexpected readmissions of patients increase by 5% and reported incidents with harm to patients by 7% respectively. Providers respond to missing EU nurses by hiring UK nurses and fostering promotions in the short run, and by recruiting non-European nurses in the long run.
Keywords: J24; J61; I18; 330; skilled labour shortage; public healthcare; e-/immigration; Brexit